Комплексні біоархеологічні дослідження матеріалів з розкопок на території Києво-Печерського заповідника у 2016 р. - Тараненко, С.; Горбаненко, С.; Ковальчук, О.; Горобець, Л.; Сергєєва, М.; Пучков, П. (Місто: історія, культура, суспільство, 2017)
У публікації оприлюднено результати комплексних біоархеологічних визначень з археологічних досліджень 2016 р. споруди 1 розкопу 1 Національного Києво-Печерського історико-культурного заповідника. В публикации представлены результаты комплексных биоархеологических определений из археологических исследований 2016 г. сооружения 1 раскопа 1 Национального Киево-Печерского историко-культурного заповедника. Благодаря методу флотации получено незначительное количество палеоэтноботанических материалов (зернобобовые, также просо) и антракологических остатков (угольков сосны, а также дуба и неопределенных широколиственных). Благодаря промывке почвы получены остатки рыб (осетр российский, лещ обыкновенный, щука обыкновенная, окунь речной). Классическим способом получены более крупные остатки млекопитающих (бык домашний, овца / коза, свинья), а также птиц (гусь и курица домашние). Таким образом, получены данные, характеризующие рацион владельца сооружения 1. Однако, на данном этапе невозможно указать удельный вес тех или иных продуктов питания в рационе. Можно лишь констатировать, что продукты были достаточно обыденными, а их появление следует связать не с самой хозяйственной деятельностью по их выращиванию, а с приобретением готовых продуктов. The results of complex bio-archaeological definitions from archaeological research in 2016 (excavation 1, construction 1) on the territory of the National Kyiv-Pechersk Historical and Cultural Reserve are represented in this paper. Using the method of flotation, a small amount of palaeoethnobotanical material (leguminous plants, and millet) as well as anthracological remains (charcoal of pine and oak, indeterminate deciduous trees) was obtained. Using the screen-washing of the soil, fish remains were obtained; these bones are belonged to Russian sturgeon, common bream, northern pike and common perch. The bigger remains of mammals (cattle, sheep or goat, and pig) and birds (domestic goose and chicken) were obtained through the ‘classic’ way (i.e., during the excavations). Thus, the obtained data characterizing the diet of the holder of the construction 1 were obtained. However, it is not possible to specify the proportion of specific products in this diet at this stage of our research. It can be only concluded that they were quite ordinary, so its appearance should be caused by the acquisition of finished food; such result was probably not associated with the economic activity of cultivation of these products.